Herd behavior in the Japanese loan market: Evidence from bank panel data - Uchida, Hirofumi; Nakagawa, Ryuichi (Journal of Financial Intermediation, 2007)
This paper investigates whether Japanese banks had been following herd behavior in the domestic loan market from 1975 through 2000. Applying the technique developed by Lakonishok, Shleifer, and Vishny [Lakonishok, J., Shleifer, A., Vishny, R.V., 1992. The impact of institutional trading on stock prices, J. Finan. Econ. 32, 23–43] to the data from loans outstanding to different types of borrowers, we obtain evidence indicative of the existence of herding. City banks in Japan had been following a cyclical pattern of herding with one of the peaks around the bubble period in the late 1980s. Adjusting further for herding resulting from rational behavior, evidence indicative of the existence of irrational herding was observed only in the bubble period. Our estimate indicates that a total of some 5 trillion yen of loan increase by city banks during the period of 1987–1989 can be attributed to irrational herd behavior. The results imply that irrational bank behavior in the late 1980s might have contributed to the problems Japanese banks had with non-performing loans. We also obtained evidence for herding among regional banks and among geographically proximate banks.